Synthesis, spectroscopic and chromatographic studies of sunflower oil biodiesel using optimized base catalyzed methanolysis - Naureen, Rizwana; Tariq, Muhammad; Yusoff, Ismail; Khan Chowdhury, Ahmed Jalal; Ashraf, Muhammad Aqeel (ELSEVIER SCIENCE BV, 2015)
Methyl esters from vegetable oils have attracted a great deal of interest as substitute for petrodiesel to reduce dependence on imported petroleum and provide an alternate and sustainable source for fuel with more benign environmental properties. In the present study biodiesel was prepared from sunflower seed oil by transesterification by alkali-catalyzed methanolysis. The fuel properties of sunflower oil biodiesel were determined and discussed in the light of ASTM D6751 standards for biodiesel. The sunflower oil biodiesel was chemically characterized with analytical techniques like FT-IR, and NMR (1H and 13C). The chemical composition of sunflower oil biodiesel was determined by GC–MS. Various fatty acid methyl esters (FAMEs) were identified by retention time data and verified by mass fragmentation patterns. The percentage conversion of triglycerides to the corresponding methyl esters determined by 1H NMR was 87.33% which was quite in good agreement with the practically observed yield of 85.1%.